PROFESSIONAL ORIENTATION OF THE YOUTH OF THE NEW UZBEKISTAN: POPULARIZING THE STUDY OF FOREIGN LANGUAGES AMONG YOUNG PEOPLE, TOWARDS A NEW ERA - Arslanov Zafar Doniyorovich (International Journal of Business, Law and Political Science, 2024)
In the new era of Uzbekistan, determining the professional direction of young people, special attention is paid to their learning of foreign languages. Knowledge of foreign languages ​​is an important factor for competitiveness in the modern global economy. This study examines the importance of learning foreign languages ​​among young people, their role in achieving their professional goals, and how the educational process can be developed using modern technologies. As global interconnectedness increases, mastering foreign languages ​​​​is becoming an important skill that provides significant cultural, educational, and professional advantages for young people. This article examines how the popularization of foreign language learning among young people can be raised to a new qualitative level by integrating technology, increasing cultural relevance, and promoting multilingualism as a social norm. It highlights the role of immersive learning tools, policy support, and global youth networks in creating a multilingual future.